Misykat Cahaya Spiritualitas dalam Seni Tauhid - Teguh Agus Priyanto; Supriatna Supriatna; Benny Yohannes T. (Pascasarjana ISBI Bandung, 2021)
‘Misykat Cahaya’ is an artwork inspired by personal spiritual experiences about self-existence, the search for religious human beings overshadowed by the existence of God. Through qualitative research methods, the artist tries to dissect this spiritual phenomenon to fnd values that will be used as a guide in the work process. The combination of the non-fgurative style of Ismail Raji’ Al-Faruqi (Art of Tawhid) with Sartre’s Existentialism is used to show the relationship between man and his God. This combination is used to show the choice of being a free human being or who recognizes God as a source of value and provides a way to beter understand the existence of Muslim artists today. The Awareness of position as a human being who must exist at the same time as a servant leads to always build sensitivity to the surroundings. This is also regarding encounters with objects which are often underestimated and the light in which the existence is often ignored. This experience leads to awareness of the life force. The object of beads and light becomes a metaphor to reveal the veil that covers it in order to be able to fnd Allah SWT. The objects enable power to stimulate the emergence of imagination to the level of spiritual awareness, which ultimately brings awareness to the position of Muslim artists who are not autonomous.Keywords: Spirituality, Al-Faruqi Aesthetics, Sartre’s Existentialism, object, light